LIMITATION VOCABULARY CAN BE ONE OF FACTOR THE STUDENTS DO NOT WANT TO SPEAK ENGLISH - Rizka Dinda Amalia; Anita Anggraeni (PROJECT (Professional Journal of English Education), 2021)
English is an International language that is used as an instrument to communicate. As a foreign language it is quite normal if  English difficult to learn, because the way to write and read or speak English language is dissimilar whereas  in Indonesian language the way to read or speak and write it is the same. Same as student in one of Junior High school in Lembang, some of them do not want to speak English language especially in from of the class. The author guest one of the factor students do not want to speak English is limitation vocabulary. In this article the author try to know is it true that limitation vocabulary is one of factor student do not want to speak English ? To answer that question, the author use qualitative method through questionnaire and interview for second grade student. The result finding that many factor student do not want to speak English one of them is limitation vocabulary, the student said that is no easy to memorize a lot of vocabulary, when they memorize it the feel bored. To make the student do not feel bored the author  suggest to use some games in the class to make the student more attractive. Keywords:  Vocabulary, Factor, Speaking